2021
DOI: 10.1007/s12649-021-01640-6
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Hemp Stalk Waste Through Thermochemical Conversion for Energy and Electrical Applications

Abstract: The presented research aimed at finding new ways to value hemp by-products (stalks) from the cannabidiol industry through thermochemical conversion. Chemical and elemental composition of hemp biomass was investigated by successive chemical extractions and Scanning Electron Microscopy along with Energy-dispersive X-ray Spectroscopy. Proximate and elemental analyses completed the chemical characterization of the hemp biomass and its biochar. Thermogravimetric analysis of the hemp biomass allowed to understand it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 64 publications
2
25
0
1
Order By: Relevance
“…Thus, the improvement in thermal resistance is due to the high cellulose content in hemp fibers. Indeed, Marrot et al [ 17 ] reported a 77–80% w /r w cellulose of the dry material. Thus, the improvement in thermal resistance is due to the high cellulose content in hemp fibers, which decomposition temperature range is higher than the PLA’s one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the improvement in thermal resistance is due to the high cellulose content in hemp fibers. Indeed, Marrot et al [ 17 ] reported a 77–80% w /r w cellulose of the dry material. Thus, the improvement in thermal resistance is due to the high cellulose content in hemp fibers, which decomposition temperature range is higher than the PLA’s one.…”
Section: Resultsmentioning
confidence: 99%
“…BC recently emerged as filler in polymeric composites, including thermoplastics and thermosets [ 13 , 14 ]. The attractiveness of BC lies in its superior characteristics (depending on pyrolysis conditions), such as hydrophobicity [ 15 ], electrical conductivity [ 16 , 17 ], high surface area, and porosity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial hemp ( Cannabis sativa L.—IH) is a fast-growing, non-wood plant fiber crop with low water and nutrient requirements that grows in various environmental conditions [ 26 , 27 ]. While IH seeds are currently used for oil extraction, the remaining stalks (which represent about 70% of the plant’s dry weight) have been either used in low-value applications or have just been sent to waste [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial hemp ( Cannabis sativa L.—IH) is a fast-growing, non-wood plant fiber crop with low water and nutrient requirements that grows in various environmental conditions [ 26 , 27 ]. While IH seeds are currently used for oil extraction, the remaining stalks (which represent about 70% of the plant’s dry weight) have been either used in low-value applications or have just been sent to waste [ 26 ]. Morphologically, IH stalks contain two types of fibers: bast (very long, about 10 to 20 times longer than fibers from hardwoods, softwoods, and agricultural residues) and core fibers (shorter fibers with similar physical characteristics to hardwood fibers) [ 25 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, hemp is compatible with cold climates and produces relatively large yields, of which hemp stalks are still underutilized but full of exceptionally durable cellulose fibers. 8,9 Triglycerides (vegetable oils) have shown great potential for polymer production and have even yielded commercial products such as acrylated epoxidized soybean oil (AESO). 10 While direct application of oils is challenging, relatively simple modification methods are very efficient in turning them into reactive monomers.…”
Section: Introductionmentioning
confidence: 99%